Clinical analysis of prophylactic para-aortic intensity-modulated radiation in cervical cancer. Issue 2 (February 2023) - Jin, G.; Li, K.; Niu, S.; Liu, S.; Zhang, Q.; Fan, X.
Abstract : AIM: This study aimed to compare the survival and toxicity of patients with International Federation of Gynecology and Obstetrics (FIGO) 2009 stage IB1–IIIC cervical cancer without common iliac node metastasis treated with extended-field intensity-modulated radiotherapy (EF-IMRT) or pelvic IMRT (P-IMRT). MATERIALS AND METHODS: Thirty-one patients treated with EF-IMRT and 37 patients who underwent P-IMRT were analysed retrospectively. Both groups were treated with high-dose-rate 192 Ir two-dimensional brachytherapy and concurrent chemotherapy. The chi-square test and Kaplan–Meier method were used to compare toxicity and survival between the two groups. RESULTS: The median follow-up time of EF-IMRT group and P-IMRT group was 22 and 30 months, respectively. The 3-year overall survival (OS), progression-free survival (PFS), and para-aortic lymph node metastasis-free survival (PAMFS) in the EF-IMRT group and P-IMRT group were 87% versus 74.6%, 83.6% versus 61.7%, and 96% versus 80.5%, respectively. Treatment regimens, tumour size, and radiation time were independent prognostic factors of OS and PFS. Treatment regimens, tumour size, and total equivalent dose in 2 Gy/f (EQD2) of point A were independent prognostic factors of PAMFS. Five patients in the EF-IMRT group and 14 patients in P-IMET group experienced treatment failure. The cumulative incidence of grade 3 and 4 acute leukopenia in the EF-IMRT group was 51.6%, in comparison with 27.03% in the pelvic group. No difference was found in thrombocytopenia between two groups. CONCLUSIONS: Patients with FIGO 2009 stage IB1–IIIC cervical cancer without common iliac node metastases may be benefit from EF-IMRT. Notably, EF-IMRT exhibits increased toxicity incidence; however, this remains within an acceptable range. Highlights: Patients with FIGO 2009 stage IB1-IIIB cervical cancer may be benefit from EF-IMRT. EF-IMRT is associated with reduced risk of mortality and tumor progression. EF-IMRT does not increase gastrointestinal toxicities and genitourinary toxicities.